Arabidopsis RopGEF4 and RopGEF10 are important for FERONIA-mediated developmental but not environmental regulation of root hair growth - Huang, Guo-Qiang (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.